Evidence for a narrow near-threshold structure in the J/ψ mass spectrum in B+→J/ψ K+ decays - Aaltonen, T; Adelman, J; Akimoto, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
Evidence is reported for a narrow structure near the J/ψ threshold in exclusive B+→J/ψ K+ decays produced in p̄p collisions at s=1.96TeV. A signal of 14±5 events, with statistical significance in excess of 3.8 standard deviations, is observed in a data sample corresponding to an integrated luminosity of 2.7fb-1, collected by the CDF II detector. The mass and natural width of the structure are measured to be 4143.0±2.9(stat) ±1.2(syst)MeV/c2 and 11.7-5.0+8.3(stat)±3.7(syst)MeV/c2. © 2009 The American Physical Society.